FOUNDATION OF THE NEW RAILWAY BRIDGE OVER THE NOSICKÁ DAM ON THE RIVER VÁH - Maroš Zaťko (Acta Polytechnica CTU Proceedings, 2021)
The new railway bridge over the Nosická dam is a part of the complex modernization of the railway corridor from Púchov to Žilina. Our company participated on the project using a wide variety of special foundation techniques on artificial islands for piers P6, P5, P4 and P3 and the pillar foundations. We applied the many years of experience gained by our company through working on projects involving water. Bored piles, as well as vibrated sheet piles, welding and assemblage work have all been carried out from a floating pontoon platform and also there was jet grouting applied to stabilize embankments. At the same time we provided active assistance with temporary floating bridges and platforms for the kind of transfer on water required by our client.